2016
DOI: 10.1097/md.0000000000003109
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and Functional Evaluation of Central Lymphatics With Noninvasive Magnetic Resonance Lymphangiography

Abstract: Accurate assessment of the lymphatic system has been limited due to the lack of optimal diagnostic methods. Recently, we adopted noncontrast magnetic resonance (MR) lymphangiography to evaluate the central lymphatic channel. We aimed to investigate the feasibility and the clinical usefulness of noninvasive MR lymphangiography for determining lymphatic disease.Ten patients (age range 42–72 years) with suspected chylothorax (n = 7) or lymphangioma (n = 3) who underwent MR lymphangiography were included in this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…Evaluation of abdominal and retroperitoneal lymphatic abnormalities, including lymphatic leaks, using MRI lymphography with heavily T2-weighted fast spin echo sequences [ 10 ]. Nonenhanced MRI lymphangiography is a safe and effective method for imaging the central lymphatic system, and can contribute to differential diagnosis and appropriate preoperative evaluation of chylothorax or lymphangioma [ 13 ]. However there been few reports have described its use in chyluria patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of abdominal and retroperitoneal lymphatic abnormalities, including lymphatic leaks, using MRI lymphography with heavily T2-weighted fast spin echo sequences [ 10 ]. Nonenhanced MRI lymphangiography is a safe and effective method for imaging the central lymphatic system, and can contribute to differential diagnosis and appropriate preoperative evaluation of chylothorax or lymphangioma [ 13 ]. However there been few reports have described its use in chyluria patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…MR lymphangiography has many distinct advantages over other popular techniques used to depict lymphatics, such as fluorescent lymphangiography with indocyanine green. For example, (31,32), or susceptibility-weighted imaging could achieve similar results in patients with lymphedema. However, in general, we did not see the small-caliber extremity lymphatic channels seen on contrastenhanced MR lymphangiograms on our three-dimensional T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard for localizing lymph leakage is direct visualization at surgery or by lymphangiography. Specifically, case series have indicated that noncontrast magnetic resonance (MR) lymphangiography provides accurate visualization of the central thoracic lymphatics and sites of chyle leakage [12]. Dynamic contrast-enhanced MR lymphangiography with intranodal injection of a gadolinium-based contrast agent into the inguinal lymph nodes has also been reported to provide good spatial and temporal resolution for visualizing the anatomy and flow characteristics of the central lymphatic system [13].…”
Section: Discussionmentioning
confidence: 99%